A Hyperpolarizable 1H Magnetic Resonance Probe for Signal Detection 15 Minutes after Spin Polarization Storage. (15th November 2016) - Roy, Soumya S.; Norcott, Philip; Rayner, Peter J.; Green, Gary G. R.; Duckett, Simon B.
Abstract: Nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) are two extremely important techniques with applications ranging from molecular structure determination to human imaging. However, in many cases the applicability of NMR and MRI are limited by inherently poor sensitivity and insufficient nuclear spin lifetime. Here we demonstrate a cost‐efficient and fast technique that tackles both issues simultaneously. We use the signal amplification by reversible exchange (SABRE) technique to hyperpolarize the target 1 H nuclei and store this polarization in long‐lived singlet (LLS) form after suitable radiofrequency (rf) pulses. Compared to the normal scenario, we achieve three orders of signal enhancement and one order of lifetime extension, leading to 1 H NMR signal detection 15 minutes after the creation of the detected states. The creation of such hyperpolarized long‐lived polarization reflects an important step forward in the pipeline to see such agents used as clinical probes of disease.